The Sanya Incoherent Scatter Radar Tristatic System and Initial Experiments - Xinan Yue; Baiqi Ning; Lin Jin; Feng Ding; Changhai Ke; Junyi Wang; Ning Zhang; Yihui Cai; Mingyuan Li; Junhao Luo; Weiping Chen; Yunxia Zhang; et al. (Space Weather)
Abstract Low latitude ionosphere experiences complex dynamical and electrodynamical processes, which make the spatiotemporal variations of the corresponding electron density complicated and therefore influence trans‐ionosphere radio communications. The monitoring of low latitude dynamical drivers, such as neutral wind and ionospheric electric field, is essential for both dynamic mechanism investigations and applications. The Sanya Incoherent Scatter Radar Tristatic System (SYISR‐TS) was proposed with the main objective of low latitude ionospheric monitoring and investigation and has been successfully developed over the past decade. The system consists of the Sanya (18.3°N, 109.6°E) trans‐receiving main station with key parameters of ∼1,600 m2 antenna aperture, >4 MW peak power, <120 K system noise temperature, and ∼46 dBi normal gain, and Danzhou (19.5°N, 109.1°E) and Wenchang (19.6°N, 110.8°E) receiving only stations with key parameters of ∼790 m2 antenna aperture, <130 K system noise temperature, and ∼43 dBi normal gain. Three stations form a quasi‐equilateral triangle at Hainan Island and use Global Navigation Satellite System satellite common view technique to achieve the time synchronization with the uncertainty of the timing and time synchronization less than 50 and 10 ns, respectively. Initial collaborative satellite tracking and ionospheric common volume experiments among three stations have confirmed the detection ability of SYISR‐TS and the feasibility of achieving its scientific goals in the future.